Early life exposure to triphenyl phosphate: Effects on thyroid function, growth, and resting metabolic rate of Japanese quail (Coturnix japonica) chicks. (October 2019) - Guigueno, M.F.; Head, J.A.; Letcher, R.J.; Karouna-Renier, N.; Peters, L.; Hanas, A.M.; Fernie, K.J.
Abstract: Triphenyl phosphate (TPHP; CAS # 115-86-6), a commonly used plasticizer and flame retardant, has been reported in wild birds and identified as a potential high-risk chemical. We exposed Japanese quail ( Coturnix japonica ) by in ovo injection, and once hatched, orally each day for 5 days to safflower oil (controls) or TPHP dissolved in vehicle at low (5 ng TPHP/g), mid (50 ng TPHP/g), or high (100 ng TPHP/g) nominal TPHP doses. The low TPHP dose reflected concentrations in wild bird eggs, with mid and high doses 10x and 20x greater to reflect potential increases in environmental TPHP concentrations in the future. Despite no effects on mRNA expression in thyroid-related genes, TPHP exposure enhanced thyroid gland structure in high TPHP males, but in females, suppressed thyroid gland structure and activity (all TPHP females), and circulating free triiodothyronine (high TPHP females only). Consistent with thyroidal changes, and compared to controls, mid and high TPHP chicks experienced significantly reduced resting metabolic rate (≤13%) and growth (≤53%); mid TPHP males and high TPHP females were significantly smaller. The observed thyroidal effects and suppressed growth and metabolic rate of the quail chicks suggest that TPHP may adversely affect the health of wild birds. Graphical abstract: Image 1 Highlights: Japanese quail were exposed to TPHP concentrations in ovo and post-hatch for 6 days. Low exposure to TPHP reflected TPHP concentrations reported in wild bird eggs. Sex-specific effects were evident in thyroid gland structure, activity, plasma T3. Chick growth and metabolic rate was suppressed by TPHP, especially in females. Results suggest possible adverse effects of TPHP on wild bird health. Abstract : Environmentally relevant concentrations of TPHP alter avian thyroid function, growth and metabolic rate, with sex-specific effects evident.